Training Model untuk Meningkatkan Keterampilan dalam Teknik Putar - Icuk Trisetyanto (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
The objective of this research is to describe the impact of Training Model strategies in learning the material of Rotary Technique in ceramic grade XII SMKN 5 Malang. The research method is classroom action research. The subject of this reseach are 16 students of class XII Dispro Keramik at SMK Negeri 5 Malang .This reseach has two cycles, each cycle consists of four stages: (1) preparing an action, (2) taking action, (3) observation, (4) reflection. Training Model has five components: (1) clarification of objectives, (2) theoretical explanation, (3) performance, (4) simulation practice and (5) transfer training .This reseach can increase the academic achievement that can be seen by comparing the results of learning in cycle 1 and cycle 2. The performance test and observation sheets are the instruments which were used. Based on the results of reseach suggest that scored ≥ 7.78 increased from 14 students in cycle 1 to 16 students in cycle 2. It can be concluded that Training Model strategies can understand the concepts and improve student’s learning outcomes in the material of Rotary Technique in SMKN 5 Malang.